Variations of external workload across a soccer season for starters and non-starters - Nobari, Hadi (2021)
The aims of this study were to (i) analyze within-group (starters and non-starters) for the weekly acute (wAW), chronic (wCW), and acute:chronic workload ratio (wACWR) throughout the pre-, early-, mid-, and end-season periods, and (ii) analyze the within-group differences for the weekly total distance (wTD), sprint total distance (wSTD), high-speed running distance (wHSRd), and repeated sprint (wRS) throughout the soccer season. The study included a professional soccer team that participated in the highest level of the Iranian Persian Gulf Pro League during a full season. A Global Positioning System was used for data collection during the study. Results revealed significant differences between season periods for wAW and wACWR for both starters (wAW: p = 0.003, ηP2 = 0.541; wACWR: p < 0.001, ηP2 = 0.964) and non-starters (wAW: p < 0.001, ηP2 = 0.696; wACWR: p < 0.001, ηP2 = 0.943). Only non-starters had meaningful differences for wCW (p = 0.009, ηP2 = 0.408). There were significant differences in wTD and wSTD for both starters (wTD: p < 0.001, ηP2 = 0.810; wSTD: p = 0.014, ηP2 = 0.457) and non-starters (wTD: p < 0.001, ηP2 = 0.895; wSTD: p < 0.001, ηP2 = 0.781). Only non-starters showed significant differences (p < 0.001, ηP2 = 0.722) for wRS, while both groups showed no significant differences for wHSRd. In conclusion, these results revealed that both groups experienced significant differences in wAW, wACWR, wTD, and wSTD, while non-starters presented significant differences in wCW and wRS. Coaches should consider these group differences when planning training sessions. Exposure to wSTD and wRS should be addressed for non-starters, as well as fatigue monitoring for starters, especially for players with full match participation.